2020
DOI: 10.3390/s20143920
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mine Cage Safety Monitoring Algorithm Utilizing Visible Light

Abstract: The mine cage has an important role in the production of coal mines. It has many safety problems in the transportation of people, such as overloading of personnel and illegal outreach of human limbs. However, the harsh mine environment makes it very difficult to monitor personnel overload and limb extension. To solve these two problems, we propose a novel safety monitoring algorithm of the mine cage based on visible light. With visible light technology, our algorithm cleverly utilizes the existing underground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…14] has safety several safety problems such as overloading with people/trolleys or accidents caused by the outreach of human limbs. In [408], Yang et al proposed a solution using existing lighting equipment and equipping the mine cage and miners' helmets with cheap LEDs/PDs. Each transceiver broadcasts its PWM modulated information over a dedicated frequency that also represents the transceiver's identity.…”
Section: B Owc-iogt Applicationsmentioning
confidence: 99%
“…14] has safety several safety problems such as overloading with people/trolleys or accidents caused by the outreach of human limbs. In [408], Yang et al proposed a solution using existing lighting equipment and equipping the mine cage and miners' helmets with cheap LEDs/PDs. Each transceiver broadcasts its PWM modulated information over a dedicated frequency that also represents the transceiver's identity.…”
Section: B Owc-iogt Applicationsmentioning
confidence: 99%
“…13] has safety several safety problems such as overloading with people/trolleys or accidents caused by the outreach of human limbs. In [377], Yang et al proposed a solution using existing lighting equipment and equipping the mine cage and miners' helmets with cheap LEDs/PDs. Each transceiver broadcasts its PWM modulated information over a dedicated frequency that also represents the transceiver's identity.…”
Section: B Owc-iogt Applicationsmentioning
confidence: 99%
“…Xiao et al studied the current status of underground coal gasification monitoring and control and investigated some problems that still exist, as well as proposed an IoT-based monitoring system sensing platform and an optimal control model based on deep learning [16]. Pang et al proposed a new mining cage safety monitoring algorithm that uses visible light technology to monitor the human body to ensure the safety of all miner's situations [17]. Zhao et al used the Suiqi coalfield in North China to evaluate the threat level of coal seam water content to coal mine driving using hierarchical analysis and fuzzy variable set theory, and the results showed that there are geographical differences in coal seam water content and the coal mining hazard factor in the eastern region is greater than that in the western region [18].…”
Section: Introductionmentioning
confidence: 99%